A Study on Enhancing the Adaptability and Satisfaction of Expatriate Employees Through Health and Welfare Strategies in Human Resource Management - Su, Decan (Transactions on Economics, Business and Management Research, 2024)
When multinational companies assign employees to international roles, they often prioritize performance indicators and overlook the health and well-being of their expatriates. The aim of the present study is to highlight the importance of health and well-being policies for expatriates and multinational companies and to explore how such strategies can enhance expatriates’ adjustment and satisfaction. Through a systematic literature review and qualitative analysis, this study examined several high-quality studies on expatriate adjustment and satisfaction. The findings show that organizational support, self-regulation, and job adjustment have a significant impact on employees’ adaptation. However, these findings are often based on fixed employee samples, which limits their generalizability and long-term applicability. By empirically validating a theoretical model of employee well-being, combined with HRM strategies from an internationally renowned multinational company, this study fills a gap in existing research and highlights the important role of health and well-being strategies in expatriate employee adjustment and satisfaction.